Simplify the expression:  `(2sqrt(3)sqrt(36))`  2 square root 3 square root 36

Expert Answers
mathsworkmusic eNotes educator| Certified Educator

As user durbanville says, a square root can have a negative or positive result.

So `2sqrt(3)sqrt(36) = 2(-sqrt(3))(-sqrt(36))` or `2(-sqrt(3))(+sqrt(36))` or `2(+sqrt(3))(-sqrt(36))` or `2(+sqrt(3))(+sqrt(36))`

Now `sqrt(36) = sqrt(6^2) = (6^2)^(1/2) = 6^(2(1/2)) = 6`

So `2sqrt(3)sqrt(36) = +2(6)sqrt(3)` or `-2(6)sqrt(3)` or `-2(6)sqrt(3)` or `+2(6)sqrt(3)`

Only two of these are unique so

`2sqrt(3)sqrt(36) = +2(6)sqrt(3)` or `-2(6)sqrt(3)`

durbanville eNotes educator| Certified Educator

`2sqrt(3) sqrt(36)` is not an equation so you can only simplify it. To be an equation, it would have an equal sign (=) and a variable (such as 'x' to solve).

`2sqrt(3) sqrt(36)`      A square root can have a negtive or positive result

= `2sqrt3. 6`  or `2sqrt(3) (-6)`

= `12sqrt(3)` or `-12sqrt(3)`

Access hundreds of thousands of answers with a free trial.

Start Free Trial
Ask a Question